Social Psychology / Eleventh Edition - Baron Robert A.; Branscombe Nyla R; Byrne Donn Erwin (Pearson Education Limited, 2006)
The Field of Social Psychology: How We Think about and Interact with Others, Social Cognition: Thinking about the Social World, Social Perception: Perceiving and Understanding Others, Attitudes: Evaluating the Social World, The Self: Understanding ''Who Am I ?'', Prejudice: Its Causes and Effects and Cures, Interpersonal Attraction: Meeting and Linking and Becoming Acquianted, Close Relationships: Family and Friends and Lovers and Spouses, Social Influence: Changing Others' Behavior, Propocial Behavior: Helping Others, Aggression: Its Nature and Causes and Control, Groups and Individuals: The Consequences of Belonging, Social Psychology in Action: Applications to Law and Health, Social Psychology Goes to Work: Applying Social Psychology to Work Settings and Entrepreneurship.